Effect of structural funds on housing market sustainability development - correlation, regression and wavelet coherence analysis - Łukasz Mach; Karina Bedrunka; Anna Kuczuk; Marzena Szewczuk-Stępień (Risks, 2021)
Effective acquisition of funds, including European Union (EU) funds, designated for example, creating economic and social processes, may have a real impact on the elimination of the negative outcomes of the current position of the EU on the global scale. The aim of the research is to indicate the impact of spending funds from the Regional Operational Program of the Opolskie Voivodeship 2014-2020 (ROP OV) on a key macroeconomic area of the economy, i.e., the housing development sector in the region. The practical aim is to formulate recommendations and solutions that can offer guidelines for more effective spending of EU funds and their effect on the macroeconomic dimensions of the economy. The article proposes an innovative approach to linking EU payments in the region with the real estate market. The results of the research and the analyses made on this basis showed a positive impact of the payments made from the ROP OV on selected macroeconomic indicators, i.e., the number of permits issued for the construction of new apartments and the number of currently implemented housing investments. The obtained results should be used in the decision-making process at the level of regional and national authorities responsible for the payment of EU funds. In this article, prior to the research process, a literature review was made. It covered various aspects of the evolution and development of research in the area of regional development. The research process was based on innovative methods of time variability analysis, correlation between the investigated determinants and coherence analysis for the studied dimensions. Data on payments from the ROP OV concern the years 2015-2020.
Keywords: 330; regional development; EU resources; housing development market; sustainable development